"I don't think a lot of people respect us" – police and social worker experiences of interagency working with looked-after children. Issue 1 (2nd January 2023) - Kaip, Dennis; Ireland, Lana; Harvey, Joel
ABSTRACT: This original qualitative study investigated the experiences of police and social workers who worked closely with Looked-after Children (LAC) and each other in an inter-agency capacity. Participants were based in different local councils and police stations across various regions in Scotland including rural communities and the Northern Isles. Semi-structured interviews were conducted with an experienced cohort (n = 12). Those participants, police (n = 6) and social workers (n = 6), occupied different roles within their disciplines. The interview findings elicited three distinct main themes including numerous instances of traumatic experiences in working with LAC, some conflict in inter-agency working, and a lack of formal support in the workplace. The practical implications of those findings are discussed.